Influence of home chaos on preschool migrant children’s resilience: A moderated mediation model - Zhao, Jinghui; Cui, Haiyan; Zhou, Jing; Zhang, Limin (Frontiers in Psychology, 2023)
Increasing attention has been drawn to the development of preschool migrant children’s resilience recently. Resilience refers to the positive internal strengths and qualities of individuals in adverse situations, and is an essential psychological quality for preschool migrant children to cope with adversity. Home chaos as a risk factor, has an important impact on the development of individual's resilience, but the specific mechanisms under which home chaos works have yet to be explored, especially for preschool migrant children. Based on resilience model theory, 3135 preschool migrant children and their families were surveyed and a moderated mediating effect mode was constructed to test the effect of home chaos on preschool migrant children’s resilience. The results showed that after controlling for gender and age, home chaos significantly and negatively predicted preschool migrant children’s resilience. Family resilience played a mediating role in the relationship between home chaos and preschool migrant children’s resilience. Meanwhile, social support positively moderated the mediating effects of family resilience. The findings of this study suggested that low home chaos was conducive to promoting family resilience, which in turn fostered children’s resilience, and that social support could play its protective role in weakening the negative effects of home chaos and this had certain guiding implications for the development of resilience in preschool migrant children.